2015
DOI: 10.1600/036364415x688718
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeny and Character Evolution of Papaveraceae s. l. (Ranunculales)

Abstract: To explore the taxonomic status, phylogenetic patterns, and character evolution of various groups within Papaveraceae s. l. (Pteridophylloideae, Papaveroideae, Hypecoideae, and Fumarioideae), two data sets were created and analyzed using Bayesian inference, maximum likelihood, and parsimony methods: 1) a Ranunculales data set for 82 genera representing all of the major families within the order using three chloroplast DNA regions (atpB, rbcL, and matK) and nuclear 26S ribosomal DNA, and 2) a Papaveraceae s. l.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(55 citation statements)
references
References 49 publications
2
27
0
Order By: Relevance
“…Glaucium flavum and D. franchetianum were previously excluded from the Chelidonioideae based on the analysis of nuclear DNA markers (Blattner and Kadereit 1999). However, based on chloroplast DNA regions, Hoot et al (1997Hoot et al ( , 2015 suggested that Glaucium and Dicranostigma are well supported as a part of the Chelidonioideae. In our samples, these two species possessed exarillate seeds but the rest of the taxa had arillate seeds.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Glaucium flavum and D. franchetianum were previously excluded from the Chelidonioideae based on the analysis of nuclear DNA markers (Blattner and Kadereit 1999). However, based on chloroplast DNA regions, Hoot et al (1997Hoot et al ( , 2015 suggested that Glaucium and Dicranostigma are well supported as a part of the Chelidonioideae. In our samples, these two species possessed exarillate seeds but the rest of the taxa had arillate seeds.…”
Section: Discussionmentioning
confidence: 99%
“…However, on the basis of combined molecular and morphological analyses (Hoot et al 1997), and recent phylogeny and character evolution of Papaveraceae s.l. based on chloroplast DNA and nuclear 26S rDNA, Hoot et al (2015) found Glaucium and Dicranostigma to be part of Chelidonioideae in spite of their exarillate seeds. Outgroup taxa were selected on the basis of the analysis of the ITS region of nuclear ribosomal DNA by Blattner and Kadereit (1999).…”
Section: Introductionmentioning
confidence: 99%
“…Both groups showed patterns consistent with escape‐and‐radiate evolution in the sister comparisons – that is, greater species richness in canal‐bearing clades (Table ) – providing good candidate groups to test for linked evaluate the putative relationship between diversification and trait evolution. Defensive traits are also well documented for both of these groups: laticifers across Papaveraceae (Hoot, Wefferling, & Wulff, ) and laticifers and resin canals across Araceae (Cusimano et al, ; French, , ).…”
Section: Methodsmentioning
confidence: 97%
“…Molecular data for 11 taxa (obtained from GenBank) were added to the dataset of Hoot, Wefferling, and Wulff (2015) for a total of 98 taxa at four loci: three chloroplast (cpDNA) loci (atpB, matK and rbcL) and one nuclear ribosomal region (26S ; Table S1.1 and Appendix S1.3).…”
Section: Ranunculales Phylogeny and Divergence Time Estimatesmentioning
confidence: 99%